Conservation Laws, Hodograph Transformation and Boundary Value Problems of Plane Plasticity - Senashov, S.I.; Yakhno, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
For the hyperbolic system of quasilinear first-order partial differential equations, linearizable by hodograph transformation, the conservation laws are used to solve the Cauchy problem. The equivalence of the initial problem for quasilinear system and the problem for conservation laws system permits to construct the characteristic lines in domains, where Jacobian of hodograph transformations is equal to zero. Moreover, the conservation laws give all solutions of the linearized system. Some examples from the gas dynamics and theory of plasticity are considered.